NICOTINE ALTERS CAFFEINE BEHAVIORAL DEPENDENCE PATTERN: A STUDY OF CONDITIONED PLACE PREFERENCE - Pramastya, Hegar; Anggadiredja, Kusnandar (Acta Pharmaceutica Indonesia, 2011)
Caffeine and nicotine are widely used addictive substances in the world. Several studies have confirmed that nicotine could increase the caffeine intake. Animal studies also indicated that nicotine could enhance caffeine dependence behavior especially with low doses of caffeine. However, study about the behavioral interaction of caffeine and nicotine with its effect on reinstatement is still limited. This experiment was conducted for studying the interaction between nicotine and caffeine in terms of their dependence behaviors. Conditioned place preference (CPP) paradigm was used for establishing the dependence model. Forced swim test (FST) was carried out to observe any effect of caffeine and its combination with nicotine on depressive signs. A lower dose of caffeine (5 mg/kg) induced preference behavior. However, high dose of caffeine (50 mg/kg) stimulated aversive behavior indicated by decreasing preference score. Nicotine injection had no significant effect on the lower dose of caffeine. However at the high dose of caffeine, 0.7 mg/kg of nicotine i.p reduced the aversive behavior and changed the extinction-relapse behavioral pattern resulted from 50 mg/kg of caffeine. Moreover, high dose of caffeine (50 mg/kg i.p) resulted in anxiety behavior and also hyperkinesia shown by lower immobility time in FST. Nicotine injection prior to the high dose of caffeine reduced the anxiety-hyperkinesia manifestation. The result from the current study suggests that nicotine could alter the expression of behavioral manifestation of caffeine, especially with the higher dose of caffeine.